2016
DOI: 10.1002/2016jd025471
|View full text |Cite
|
Sign up to set email alerts
|

Ambient observations of hygroscopic growth factor and f(RH) below 1: Case studies from surface and airborne measurements

Abstract: This study reports a detailed set of ambient observations of optical/physical shrinking of particles from exposure to water vapor with consistency across different instruments and regions. Data have been utilized from (i) a shipboard humidified tandem differential mobility analyzer during the Eastern Pacific Emitted Aerosol Cloud Experiment in 2011, (ii) multiple instruments on the NASA DC‐8 research aircraft during the Studies of Emissions, Atmospheric Composition, Clouds and Climate Coupling by Regional Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 84 publications
3
24
1
Order By: Relevance
“…Figure 3 (bottom) shows a histogram of the observed ratio of wet-to-dry modal scattering when the wet SP2 was sampled at 90% RH (functionally equivalent to f(RH) 90 measured at 1064 nm). The mean ratio is 1.02, indicating little water uptake by wildfire BC in aggregate, in general agreement with Shingler et al [2016b] who report little water uptake for size-selected bulk biomass burning aerosol during SEAC 4 RS. Martin et al [2013] reported collapse of fractal carbon aggregates in fresh emissions from several combustion sources upon humidification, which would result in a reduction in scattering following humidification.…”
Section: Aggregate Observations Of All Identified Plumessupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 3 (bottom) shows a histogram of the observed ratio of wet-to-dry modal scattering when the wet SP2 was sampled at 90% RH (functionally equivalent to f(RH) 90 measured at 1064 nm). The mean ratio is 1.02, indicating little water uptake by wildfire BC in aggregate, in general agreement with Shingler et al [2016b] who report little water uptake for size-selected bulk biomass burning aerosol during SEAC 4 RS. Martin et al [2013] reported collapse of fractal carbon aggregates in fresh emissions from several combustion sources upon humidification, which would result in a reduction in scattering following humidification.…”
Section: Aggregate Observations Of All Identified Plumessupporting
confidence: 89%
“…The mean ratio is 1.02, indicating little water uptake by wildfire BC in aggregate, in general agreement with Shingler et al . [] who report little water uptake for size‐selected bulk biomass burning aerosol during SEAC 4 RS. Martin et al .…”
Section: Resultsmentioning
confidence: 99%
“…Although many particle shapes exist in the atmosphere, such as isometric particles, platelets, and fibers, the difficulty to measure morphological properties often leads to the assumption of particle sphericity for most applications (Reist, 1993). An added complication is that particles with irregular morphology can collapse into a spherical shape upon humidification (Shingler et al , 2016). Scanning Electron Microscopy (SEM) combined with Energy Dispersive Spectrometry (EDX) provides useful information about the elemental composition, size and shape of PM, and thus is a useful technique in distinguishing particles originating from different sources (Salma et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Both properties depend on the chemical composition of the smoke and are in turn a function of fuel composition and combustion phase. Measuring aerosol water uptake is key to understanding its effects on visibility (Day et al, ), cloud condensation nuclei activity (Petters, Carrico, et al, ), and climate significance (Shingler et al, ). Two recent studies review many of the major studies globally examining the hygroscopic response of light scattering coefficient (often abbreviated f (RH)) as it relates to effects on atmospheric radiation (Dumka et al, ; Titos et al, ).…”
Section: Introductionmentioning
confidence: 99%